Physical activity in the prevention of chronic diseases of academic students - Czeczelewska, Ewa; Czeczelewski, Jan (Polish Journal of Public Health, 2013)
Academic studies cover usually a period of life between 19 and 25 years of age. It is the time of transition from living in the family home under the care of parents to becoming an independent adult. New habits developed in this period are often extrapolated to improper nutritional attitudes and inappropriate patterns of behavior that may result in health deterioration among graduates in their future lives.The meta-analysis has revealed that an unfavorable health condition of the Polish population is connected with a high incidence of chronic diseases. It calls for immediate actions aimed at identifying factors that contribute to an increasing incidence of diseases. It is justified to diagnose this phenomenon among university students burdened with such risk factors as arterial hypertension, dyslipidemia, impaired glucose tolerance or low physical activity. The population of 20-34-year-olds has low awareness of the non-pharmacological methods of preventing chronic diseases, as indicated by multicenter national studies WOBASZ and NATPOL-PLUS on health population.Health benefits of physical activity are more and more recognized and appreciated. Physical exertion influences blood pressure, improves lipid parameters, decreases insulin resistance, helps to maintain proper body mass, and improves general physical and mental state. The influence of physical exertion on the body is indisputable. Therefore, it is necessary to pay more attention to everyday spontaneous physical activity especially during studies.